2011
DOI: 10.3357/asem.3023.2011
|View full text |Cite
|
Sign up to set email alerts
|

Airport Quarantine Inspection, Follow-Up Observation, and the Prevention of Pandemic Influenza

Abstract: Quarantine inspection at the airports, follow-up observation by local authorities, and overall concomitant efforts may have contributed to secondary infection control in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(36 citation statements)
references
References 0 publications
0
36
0
Order By: Relevance
“…Obtaining contact information of travelers to be used if needed for contact tracing or public health observation purposes ˅ E,I [6,26]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Obtaining contact information of travelers to be used if needed for contact tracing or public health observation purposes ˅ E,I [6,26]…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Table 4, from the 27 articles, 25 reported entry screening measures [6,7,8,9,10,11,15,20,21,23,24,26,27,28,29,31,32,33,34,35,36,37,38,39,40] and five reported exit screening measures [6,9,16,22,28]. Figures 2–4 summarize the results of entry and exit screening measures by disease and per country.…”
Section: Resultsmentioning
confidence: 99%
“…We reviewed 1 intervention study (18), 5 observational studies (6,(19)(20)(21)(22), and 10 simulation studies (Appendix Tables 9, 10). Miyaki et al (18) conducted an intervention study in Japan during 2009-2010 involving 2 companies.…”
Section: Quarantine Of Exposed Personsmentioning
confidence: 99%
“…However, the applicability of these findings is uncertain because maritime travel is uncommon in the 21st century. Conversely, Fujita et al (19) reviewed the onboard quarantine experience at Narita International Airport in Tokyo, Japan, during the influenza A(H1N1) pdm09 pandemic, and reported that the intervention detected few cases and was ineffective in preventing virus entry into the country (19).…”
Section: Quarantine Of Exposed Personsmentioning
confidence: 99%
“…Over the course of the last decade, airport authorities around the world in Australia (Eastwood et al, 2010), Canada (Johanis, 2007), Japan (Fujita et al, 2011) and Singapore (Wilder-Smith et al, 2003) have gained valuable experiences that are crucial to the formulation of effective and organised pandemic responses. These have been used as benchmarks for the development of future pandemic controls at airports.…”
Section: Practical Experiencesmentioning
confidence: 99%